2018
DOI: 10.1515/aut-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Uniformity of Thermally Bonded Points in Polypropylene Spunbonded Non-Wovens Using Image Processing and its Relationship With Their Tensile Properties

Abstract: This article aims at the image processing of surface uniformity and thermally bonded points uniformity in polypropylene spunbonded non-wovens. The investigated samples were at two different weights and three levels of non-uniformity. An image processing method based on the k-means clustering algorithm was applied to produce clustered images. The best clustering procedure was selected by using the lowest Davies-Bouldin index. The peak signal-to-noise ratio (PSNR) image quality evaluation method was used to choo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A decrease in these two indexes resulted by a lower variance represents a more uniform sample. Emadi et al also adopted Id as index for weight uniformity measurement [16] To overcome the issue with spatial resolution of CV-based methods, new works determined the spatial resolution of images with the Poisson tests. In the study by Pourdeyhimi and Kohel, images are thresholded using a fixed threshold and divided into a different number n of sub-windows and the area fraction in each is calculated [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in these two indexes resulted by a lower variance represents a more uniform sample. Emadi et al also adopted Id as index for weight uniformity measurement [16] To overcome the issue with spatial resolution of CV-based methods, new works determined the spatial resolution of images with the Poisson tests. In the study by Pourdeyhimi and Kohel, images are thresholded using a fixed threshold and divided into a different number n of sub-windows and the area fraction in each is calculated [17].…”
Section: Discussionmentioning
confidence: 99%
“…In pretrials for this work, it has also been found out that the KNN algorithm for the binarization of our images cannot converge in an acceptable time, so the result of the segmentation is not good which will mislead the analysis method. Therefore, the method described by Emadi et al [16] will also not be considered further in this article.…”
Section: Analysis Of Real Imagesmentioning
confidence: 99%